Pengaruh Stres Kerja terhadap Voluntary Turnover Intention Karyawan - Ane Emigia Kusuma; Erry Sunarya; Kokom Komariah (Journal of Management and Bussines (JOMB), 2019)
The purpose of this study is to determine the effect of work stress on employee voluntary turnover intention, with the dimensions of work stress partially and simultaneously. The use of methods in this study is to use the type of sampling included in Simple Random Sampling and by distributing questionnaires as many as 210 respondents. The data analysis technique method used is Path Analysis by using SPSS 24 Software, and for hypothesis testing is a partial statistical test (t test) and a simultaneous test (f test). The results, the t test showed that work stress through the Role Conflict dimension (X1) had a positive and not significant effect on Voluntary Turnover Intention, the Ambiguous / Unclear Role (X2) had a positive and significant effect on Voluntary Turnover Intention, Excessive Workload (X3 ) has a positive and significant effect on Voluntary Turnover Intention. Based on the F test sig value 0,000 <0,05 which means that work stress together (simultaneous) namely Role Conflict (X1), ambiguous / unclear role (X2), and excessive workload (X3) have a significant effect towards Voluntary Turnover Intention (Y). Conclusion, simultaneously job stress has a positive and significant effect on employee voluntary turnover intention at PT Doosan Sinar Sukabumi, Sukabumi Regency Keywords: Job Stress, Voluntary Turnover Intention